Arithmetic Optimization Algorithm Based on Cauchy Mutation Trigonometric Function Search to Solve Combined Economic Emission Dispatch Problem - Yun-Peng Li; Lin-Xuan Zhang; Zheng-Jie Feng (IEEE Access, 2023)
Nowadays, problems such as greenhouse effect and air pollution become increasingly prominent. The power generation process should pay attention to the fuel cost and reduce the pollution to the environment. In this paper, an arithmetic optimization algorithm (AOA) based on Cauchy mutation trigonometric function search is proposed to solve the combined economic emission dispatch (CEED) problem. The price penalty factor is used to convert multiple objective functions of CEED problem into one objective. The math optimization probability (MOP) parameter is used to control the position update of the AOA. MOP is replaced by the oscillation coefficient and Cauchy mutation, which can not only guarantee the local search accuracy but also enhance the global search capability. 6 kinds of trigonometric function search operators, sine function, hyperbolic sine, inverse hyperbolic sine, hyperbolic tangent, inverse hyperbolic tangent, are used to replace the fixed value control parameters in AOA algorithm. The algorithm still has a certain ability to jump out of the local optimal in the late running. The 23 test functions are used to verify the effect of the improved AOA method. The AOA is compared with 6 kinds of improved AOA, and the improvement method with the best effect is selected, and then compared with other intelligent optimization algorithms to verify the effectiveness of the improved strategy. In addition to improving the algorithm, the constraint of CEED problem is also treated. Five kinds of random disturbance penalty functions are proposed, which are cosine function, hyperbolic sine function, tangent function, hyperbolic tangent function and V-type function. The CEED problem of 6 units was selected for simulation experiment under 4 different load demands. The experimental data show that the arithmetic optimization algorithm based on Cauchy mutation trigonometric function search has a good effect on solving CEED problems, and the random disturbance penalty strategy is more effective in solving quality.